Polar optical phonon states and their dispersive spectra of a wurtzite nitride superlattice with complex bases: transfer-matrix method - Zhang, L. (Condensed Matter Physics, 2011)
Based on the dielectric continuum model and transfer-matrix method, the completing polar optical phonon states in a wurtzite GaN-based superlattice (SLs) with arbitrary-layer complex bases are investigated. It is proved that 2n types of phonon modes probably exist in a wurtzite nitride SL with n-layer complex bases. The analytical phonon states of these modes and their dispersive equations in the wurtzite GaN/AlxGa₁-xN SL structures are obtained. Numerical calculations on a three-layer GaN/Al₀.₁₅Ga₀.₈₅N/AlN complex bases SL are performed. Results reveal that there are interface optical (IO) phonon modes of one type only and four types of quasi-confined (QC) phonon modes in three-layer
GaN/Al₀.₁₅ Ga₀.₈₅ N/AlN complex bases SLs. The dispersive spectra of phonon modes in complex bases SLs extend to be a series of frequency bands. The behaviors of QC modes reducing to IO modes are observed. The present theoretical scheme and numerical results are quite useful for analyzing the dispersive spectra of completing phonon modes and their polaronic effect in wurtzite GaN-based SLs with complex bases. На основi дiелектричної неперервної моделi i методу трансфер-матрицi, дослiджено доповненi стани полярних оптичних фононiв у вюрцит GaN-базованiй супергратцi (СГ) зi складними базисами. Доведено, що 2n типи фононних мод iснують у вюрцит нiтриднiй СГ з n-шаровими складними базисами. Отримано аналiтичнi фононнi стани цих мод та їхнi дисперсiйнi рiвняння у структурах вюрциту GaN/AlxGa₁−xN СГ. Здiйснено числовi розрахунки на тришарових GaN/Al₀.₁₅Ga₀.₈₅N/AlN складних базисах СГ. Результати показують, що є iнтерфейснi оптичнi (IО) фононнi моди тiльки одного типу i чотири типи квазiобмежених (КО) фононних мод у тришарових GaN/Al₀.₁₅ Ga₀.₈₅ N/AlN складних базисах суперграток. Дисперсiйнi спектри фононних мод в складних базисах суперграток розширюються до низки частотних зон. Спостерiгається, що поведiнка КО мод редукується до IО мод. Ця теоретична схема i числовi результати є досить корисними для аналiзу дисперсiйних спектрiв доповнених фононних мод
i їхнiх поляронних впливiв у вюрцит GaN-базованих супергратках i з складними базисами.